Sustained Improvement of Negative Self-Schema After a Single Ketamine Infusion: An Open-Label Study - Hasler, Gregor; Suker, Samir; Schoretsanitis, Georgios; Mihov, Yoan (Frontiers in Neuroscience, 2020)
Conventional antidepressants have several important limitations, including a lack of direct effects on negative self-schema, which is at the core of Beck’s cognitive theory of depression. Based on previous studies showing a positive effect of ketamine on negative cognition, we compared reductions in negative self-schema between responders and non-responders to a single infusion of ketamine. In an open-label study, 26 participants with treatment-resistant depression received 0.5 mg/kg ketamine via infusion. Depression symptoms were assessed at baseline, 24 hours, and seven days after treatment with Montgomery-Åsberg Depression Rating Scale (MADRS) and Beck Depression Inventory (BDI-II). Nine of the 26 participants fulfilled response criteria after 24 hours. Of these, eight still fulfilled response criteria after seven days. Response was defined as a reduction in MADRS total score of 50% or more. Responders improved significantly more than non-responders both 24 hours and seven days after ketamine treatment on the following BDI-II items: item 1 (“Sadness”), item 7 (“Self-Dislike”), and item 8 (“Self-Criticalness”). These results suggest an important therapeutic effect of ketamine on negative self-schema, which is a fundamental cognitive aspect of depression. This effect is unique and might be associated with ketamine’s profound effects on neuroplasticity. Small sample size and lack of a placebo control group are the major limitations of this study.